Tuning Fischer-Tropsch synthesis product distribution toward light olefins over nitrided Fe-Mn bimetallic catalysts. (1st July 2023) - Wang, Chao; Zhu, Huaqing; Zhang, Juan; Huang, Zhijun; Chen, Jiangang
Graphical abstract: Successful nitridation of Fe-Mn bimetallic catalysts by reduction with H2 followed by NH3 treatment, which stabilizes ε′-Fe2.2 C and Fe2 N and improves light olefin selectivity. Highlights: Fe-Mn bimetallic catalysts pre-reduced by H2 that permit an easy nitrogenation. Doping with Mn and further nitriding treatment improve the content of epsilon-iron carbide. C2 = -C4 = selectivity was proportional to the content of epsilon-iron carbide. Iron carbides (χ-Fe5 C2, ε-Fe2(.2) C and θ-Fe3 C) and iron nitride (Fe2 N) to hydrocarbon selectivity was deconvolved by linear regression. Abstract: A series of Fe-Mn bimetallic catalysts with various pretreatment atmosphere including H2, CO and alternatively NH3, were employed for the Fischer–Tropsch synthesis (FTS). The structure of Fe-Mn bimetallic catalysts was revealed by using multiple characterization techniques, where Mössbauer spectra was used to define the iron species. With direct pretreatment, the reduction efficiency is in the sequence of H2  > CO > NH3 . Fe-Mn bimetallic catalysts pre-reduced by H2 that permit an easy nitrogenation. To correlate the phase compositions of spent catalysts with FTS performance, the individual contribution of Fe, iron carbides (χ-Fe5 C2, ε-Fe2(.2) C and θ-Fe3 C) and iron nitride (Fe2 N) to hydrocarbon selectivity was deconvolved by linear regression. It was discovered that C2 = -C4 = selectivity was proportional to the content of epsilon-iron carbide, which was promoted by the doping with Mn and further nitriding treatment. Successfully nitrided Fe-Mn bimetallic catalysts exhibit a better stability of C2-C4 O/P along time on stream, while either direct CO treatment or NH3 treatment followed by CO treatment result in a rapid decent of C2-C4 O/P ratio against time. Furthermore, Mn enhances long-chain hydrocarbon selectivity and suppresses CH4 formation, whereas the nitrogenation inhibits the chain growth ability, concentrating the hydrocarbon selectivity into C2-C4 fraction. Hence, the nitrided Fe-Mn catalyst is able to maintain a high light olefin selectivity. This study highlights that nitrogenation could provide an opportunity to tune the C2-C4 olefins by optimizing the phase structure of Fe-Mn catalysts.